Efektivitas Pendidikan Kesehatan Terhadap Perubahan Pengetahuan Dan Keterampilan P3k Pada Siswa Pmr Di SMA Negeri 3 Sukoharjo - Kristanto, Nova, Arina Maliya, S. Kep, M.Si. Med, Dian Hudiyawati, S. Kep, Ns (2016)
Traffic accidents are one of the biggest causes of death in Indonesia. Less of people participant in handle traffic accident, cause resulting in the death toll due to the higher accident. Actually, its can be minimalized if the people know how to give first aid. Health education is an effort or activity to help individual, groups, and others in improve their ability of knowledge, attitude, and skill to achieve a healthy life. The purpose of this research is to know the diference of the effectiveness of health education for change in knowledge and frist aid skill to PMR In SMA Negeri 3 Sukoharjo This research method ispre experiment with nonequivalent control group pretest-postest. The sample in this reseach consist of 40 respondent, divide into 2 group, there are 20 student using speech and 20 student uswing simulation. Data analysisn techniques using wilcoxxo to rate the student knowledge before and after givehealth education, while test between speech and simulation using mann-whitney test. Wilcoxxo obtained from statistical test p-value 0.001 in both groups then H0 is rejected, there are differences in blood sugar levels after therapy before both wet cupping therapy and reflexology. From the statistical test Wilcoxon obtained p-value 0.003 for group lectures before and after health education with motede lecture there are differences in the average and the group simulation results obtained p-value of 0.001, it can be concluded terdapar average difference before and after education lecture method. From the statistical test results obtained Mann-Whitney Test p-value 0.559 and the average difference in the two groups: -0.25, then H0 accepted meaning there is no difference in knowledge of lectures with group after group of simulations are given health education. While the results of skills between the lectures with simulation group showed a p-value 0.002. It means that there is a difference between the skills of lectures with group simulations, the average difference of -11.75. Skill simulation group was higher than lecture group skills.. Keywords: Teaching Methods, Simulation Method, Skills